Measurement of D*± meson production in jets from pp collisions at √s=7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
This paper reports a measurement of *± meson production in jets from proton-proton collisions at a center-of-mass energy of √s=7 TeV at the CERN Large Hadron Collider. The measurement is based on a data sample recorded with the ATLAS detector with an integrated luminosity of 0.30  pb-1 for jets with transverse momentum between 25 and 70 GeV in the pseudorapidity range |η| <2.5. *± mesons found in jets are fully reconstructed in the decay chain: *⁺→⁰π⁺ 0 →⁻π⁺, and its charge conjugate. The production rate is found to be ⁡(*±)/⁡(jet) =0.025 ±0.001⁢(stat.) ±0.004⁢(syst.) for *± mesons that carry a fraction of the jet momentum in the range 0.3 < <1. Monte Carlo predictions fail to describe the data at small values of , and this is most marked at low jet transverse momentum.